Threats and offers in community mental healthcare. - Dunn, M; Maughan, D; Hope, T; Canvin, K; Rugkåsa, J; Sinclair, J; Burns, T (2012)
Making threats and offers to patients is a strategy used in community mental healthcare to increase treatment adherence. In this paper, an ethical analysis of these types of proposal is presented. It is argued (1) that the primary ethical consideration is to identify the professional duties of care held by those working in community mental health because the nature of these duties will enable a threat to be differentiated from an offer, (2) that threatening to act in a way that would equate with a failure to uphold the requirements of these duties is wrong, irrespective of the benefit accrued through treatment adherence and (3) that making offers to patients raises a number of secondary ethical considerations that need to be judged on their own merit in the context of individual patient care. The paper concludes by considering the implications of these arguments, setting out a pathway designed to assist community mental healthcare practitioners to determine whether making a specific proposal to a patient is right or wrong.